Facilitating Peer Interaction Regulation in Online Settings: The Role of Social Presence, Social Space and Sociability - Vrieling-Teunter, Emmy; Henderikx, Maartje; Nadolski, Rob; Kreijns, Karel (Frontiers in Psychology, 2022)
A plethora of studies stress students’ self-regulated learning (SRL) skills to be conditional for successful learning in school and beyond. In general, self-regulated learners are actively engaged in constructing their own understanding also including the regulation of contextual features in the environment. Within the contextual features, the regulation of peer interaction is necessary, because college courses increasingly require peer learning. This goes along with the increasing interest for online learning settings, due in no small part to the recent Covid-19 pandemic. In the present study we explore how social presence (i.e., the degree to which the other person is perceived as physical ‘real’), social space (i.e., trust building between peers) and sociability (i.e., the degree to which the virtual learning environment supports social presence and social space) are essential elements in the regulation of online peer interaction.. To shed light in this matter, higher education students were qualitatively followed for one year in an online academic writing course by using) retrospective interviews (n=7) and reflective questions (n=62). Additionally, for social presence, students’ perceptions were quantitatively measured with a validated questionnaire (n=41). The results show that the planning phase is the most important phase for supporting students’ social presence because that is where the regulation of peer interaction becomes important. The sociability has an important role here as well becoming less prominent further on in the self-regulation process. In the SRL follow-up phases, students look for other ways to increase their social presence and social space in order to shape the regulation of peer interaction from a position of trust. In the evaluation phase, students are aware of the importance of social presence but less of social space for the regulation of peer interaction. We conclude with some design principles to facilitate students’ regulation of peer interaction in online settings.